Bad News Discourse in the Lithuanian Soviet Press - Gedzevičienė, Dalia (Respectus Philologicus, 2018)
[abstract in English; full article and abstract in Lithuanian]The rhetoric and the stylistics – the choice of text style, genre, and rhetorical devices – of Soviet bad news discourse is analysed in this paper. This discourse is represented by 193 reports regarding disasters, crimes, and violation of socialistic moral which were published in the daily paper Komjaunimo tiesa (eng. The Truth of the Komsomol) in 1970–1973. It was found that the bad news in the selection of official texts of this period distinguishes by a much lower register of Newspeak – unlike as in the articles of first pages, there is almost no pathos here, the militaristic metaphors are used in the text of the article only, but they cannot be seen in the headings. One of the main rhetorical devices is an irony, which is created by using phraseology, jargon, famous quotes, dialogues, etc., – everything, which looks like a daily colloquial language. The choice of text form which is more related to fiction than to journalism (essay, satire) may be treated as one of the pretexts which justify in the eyes of the readers an idea of an author to write in a different language than it was ordinary in the context of ideologized press language of that period. By using the corresponding rhetoric, they believed to accomplish the propagandistic aim of these texts more efficiently – to suggest an image of more safe, democratic, successful, and self-critical country than it really was.
Keywords: The Soviet Period, Newspeak, Rhetoric, Bad News, Discourse